Field notes on Elkei - Elgh, Erik; Persson, Rasmus (Nusa, 2024)
Elkei is a severely understudied language spoken in Sandaun Province, Papua New Guinea. Here, almost 200 lexical items, mainly nouns, a more than threefold increase in the amount of published material on the language, are presented. A phonology is proposed based on minimal pairs, restrictions on syllables, and acoustic analysis. Number and gender declension strategies are also investigated, with some comparison to the closest relative, Olo.